Corporate culture and its impact on employees' attitude, performance, productivity, and behavior: An investigative analysis from selected organizations of the United Arab Emirates (UAE) - Jacob Cherian; Vilas Gaikar; Raj Paul; Robert Pech (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
The present research paper focuses on four key aspects of organizational culture in the United Arab Emirates (UAE): employee attitude, performance, behavior, and productivity. Every organization has a unique culture, which shapes the employees' perspectives to a large extent. The greater the consistency of the approach, the greater the likelihood of that organization achieving success. The main purpose of this study was to examine the influence of corporate culture on the behavior of heterogeneous groups of employees. The UAE, as an emerging economy, has various ethnicities and nationalities in its workforce, each having its own distinctive national customs, languages, religions, histories, and work patterns. This paper examines two cases in the remittances and foreign exchange industry in the UAE as being characteristic of finance companies, comprising employees who originated from many nations working together regardless of their socio-cultural background. Based on a questionnaire, the literature, and a hypothesized model, this paper investigates the relationship of UAE's heterogeneous work culture on employees' perspectives. In an innovative way, the result of this study reveals and supports our hypotheses that organizational culture has a high impact on the work performance, attitudes, and behaviors of the employees belonging to two selected companies, regardless heterogeneous nationalities and cultures.
Keywords: 650; corporate work culture; employee attitude; performance; behavior and productivity; diversity